LANGUAGE AND THOUGHT - I. O. Gaidenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2015)
The article is aimed at the problem of language-thought interrelation which has always been of great interest to philosophers and linguists as the former is inconceivable without the latter; thus, language and thought are inseparable. Although the question of language-thought interconnection has been studied by many linguists, there is no generally accepted approach to the distinction of their interdependence and convergence. One approach to the problem, for instance, relies on regarding "language as thought and thought as language" (M. Müller), the other approach, which the article is focused on, consists in underlying their inequality even though they form organic unity (A. Potebnya). Scientific works of distinguished linguists about thought objectification have been investigated. The issues of language-experience and language-culture interrelation as well as their correspondence to the subject of the article have been analyzed. Relation of the first type is of primary significance since experience is fundamental to formation of knowledge and, therefore, culture as well as words that constitute language classes. Being component part of a specific language class each word possesses the meaning somehow connected with the type of experience the class describes; the name of the class is also general and applicable to each of its constituents. Accumulated knowledge and experience are shared by means of words, i.e. objectified in language units. Full objectification is only possible when words are combined together into meaningfully complete patterns, which makes language a communication tool. As communication may be of verbal and non-verbal forms, it cannot equate with language; however, human language and